Performance Management of The Regional Inflation Control Team Central Kalimantan Province In Inflation Control - Sembiring, Rilyane Suzan Rasita; Zulkarnain, Iskandar; Dapi, Moh. Djufri; Sukmana, Enriko Tedja (AL-QARDH, 2022)
Inflation control necessitates inter-institutional collaboration and coordination, particularly between Bank Indonesia and the government. To continue to increase cooperation, the Government and Bank Indonesia formed an Inflation Monitoring and Control Team (TPI) at the central level in 2005, followed by the establishment of a Regional Inflation Control Team (TPID) in 2008. It is vital to take strategic efforts to control and suppress inflation by forming the Central Kalimantan Regional Inflation Control Team with the collaboration of regional agencies (TPID). The goal of this article is to identify the performance management strategies used by TPID in Central Kalimantan to keep inflation under control. This study employs a qualitative descriptive method and is conducted in the field. The secretaries and members of the TPID in Central Kalimantan were the subjects of this investigation. The research data was gathered through observation, interviewing, and recording techniques, which were then validated through source triangulation and analyzed through simplification, presentation, and conclusion stages. The findings of this study show that TPID's administration of inflation control efforts in Central Kalimantan complies with Governor Regulation No. 10 of 2015's inflation control guidelines. Because the inflation control procedure carried out by the Central Kalimantan TPID is in accordance with the planning, organizing, executing, and regulating functions, the Central Kalimantan TPID indirectly performs a management function. The Central Kalimantan TPID's inflation control management was highly effective. The Central Kalimantan TPID's inflation control administration was fairly effective in keeping inflation in Central Kalimantan and Palangkaraya generally regulated and constant.